A Cooperation of Skipper-Labour Retainer on Fisherman in the Review of Akad Qardhul Hasan - Awaluddin; Ruslang (International Journal of Seocology, 2021)
In general, this research aims to determine the application of qardh in the relationship between skipper-labour retainer in the social interaction of fishermen's life in Sampulungan Village. The specific purpose of this research is to find out the analysis of qardh in the interaction between the skipper- labour retainer in the life of fishermen in Sampulungan Village with the perspective of equitable distribution of Islamic economics. This research uses descriptive qualitative research methods. The research was conducted in Sampulungan Village, North Galesong District, Takalar Regency. The approach used is the normative theological approach, phenomenology, and the Islamic economic approach. The data collection methods include interviews, observation and documentation. The collected data were analyzed through several stages, namely data reduction, data presentation, and conclusion drawing. Samples The population of this research includes skippers as ship owners, retainer as capital owners, and mustard greens as courtier workers. This population was taken from 4 hamlets of Sampulungan Village, Galesong Utara District, Takalar Regency. The results of this research indicate that the qardh contract that applies between the collectors of labour in Sampulungan Village does not violate the provisions of qardh according to the Islamic economic review.